Successful Conservative Management of Pancreatico-Colonic Fistula - Hazem Ben Ameur; Haitham Rejab; Wiem Feki; Moez Sahnoun; Rafi k Mzali; Zeineb Mnif (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2017)
Background: Internal fistula with adjacent viscera during acute pancreatitis is a rare complication. Due to their anatomic localization, colon, duodenum or stomach may be involved. Pancreatico-colonic fi stula is associated with a higher septic risk and surgery is usually mandatory. Results and main findings: We report a new case in 71-year-old man diagnosed by CT with rectal water soluble contrast media and managed conservatively. To our knowledge, this is the second case in the literature treated in this way. Conclusion: Conservative treatment may be offered to selected patients who have a rapid improvement of symptoms associated with a signifi cant regression of the collection.